2017
DOI: 10.1016/j.petrol.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of H2S solubility in aqueous NaCl solutions by molecular simulation

Abstract: The solubility of hydrogen sulfide in aqueous NaCl solutions has been investigated by calculation of Henry constants through Monte Carlo simulations and using a nonpolarizable force field. The Lorentz-Berthelot combining rules appeared the most appropriate to simulate this system compared to other usual rules. The physical behavior and the trends experimentally observed are qualitatively well reproduced by this purely predictive approach for the binary system H 2 S+H 2 O as well as for the salted system H 2 S+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 86 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Thus, Widom insertion method could appear in this context less efficient than more advanced techniques to evaluate chemical potential, such as umbrella sampling (Torrie and Valleau, 1977), slow-growth method (Nezbeda and Kolafa, 1991) or thermodynamic integration (Frenkel and Smit, 1996). Nevertheless, a prior study on the solubility of H 2 S in NaCl aqueous solution (Fauve et al, 2017) shown that, with a sufficient number of Monte Carlo steps, the Widom insertion method lead to similar results than thermodynamic integration technique within statistical uncertainties.…”
Section: Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Widom insertion method could appear in this context less efficient than more advanced techniques to evaluate chemical potential, such as umbrella sampling (Torrie and Valleau, 1977), slow-growth method (Nezbeda and Kolafa, 1991) or thermodynamic integration (Frenkel and Smit, 1996). Nevertheless, a prior study on the solubility of H 2 S in NaCl aqueous solution (Fauve et al, 2017) shown that, with a sufficient number of Monte Carlo steps, the Widom insertion method lead to similar results than thermodynamic integration technique within statistical uncertainties.…”
Section: Algorithmmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of Monte Carlo simulation to predict gas solubility in brines, such as CO 2 (Creton et al, 2018;Jiang et al, 2017;Liu et al, 2013;Tsai et al, 2016;Vorholz et al, 2004), H 2 S (Fauve et al, 2017), SO 2 and other diatomic light gases (Creton et al, 2018). However, to the best of our knowledge, no molecular simulation study dealing with the solubility of hydrogen in electrolyte solutions has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Many molecular simulation studies exhibited this structure-forming phenomenon. As an example, figure 2 shows the radial distribution functions (rdf ) in an aqueous NaCl solution at 1 mol/kg and 298.15K between the pairs Na + /O and Cl -/O (where O is the oxygen atom of the water molecules) obtained from Monte Carlo simulations [100]. Using an integral oof the rdf, this figure also shows the number of water molecules surrounding each ion, also called the coordination numbers (CN).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Radial distribution function (rdf ) and coordination number (CN)between Na + /O pairs and Cl-/O pairs obtained from Monte Carlo simulations[100] …”
mentioning
confidence: 99%
“…NaCl is the most common ion in groundwater brine, and different ion models can have a great influence on the density of solution. Fauve et al 40 used OPLS 41 + SPC/E models to simulate the density of NaCl saline solutions with different concentrations at a wide range of temperatures (from 25 to 275°C), and the average deviation between the calculation and the experimental data was 1%. However, the performance of the SPC/E model is not as good as that of the TIP4P/2005 model under reservoir conditions.…”
Section: Ion Modelmentioning
confidence: 99%